The determinant of sustainable consumption behaviour of Moslem woman in Sukoharjo - Septi Kurnia Prastiwi; Rabia Rabia (Center for Science and Technology, IAIN Surakarta, 2019)
ABSTRACT As the increasing of the public consumption pattern, it is followed by environmental pollution offset, which is increasingly alarming. This study aims to analyze how sustainable consumption behavior of Muslim women mediates the intention to behave. Two variables that are thought to influence the sustainable consumption behavior are environmental value and environmental sensitivity by mediating behavioral intention. This study uses a survey method with a population of Muslim mothers in the Sukoharjo area, a sample of 100 respondents, with sampling using a purposive technique, namely judgment sampling, and questionnaires with 12 indicator indicators. The results of the validity, reliability, and classical assumption tests support the continuing research. Results from the path analysis show that the variable ‘environmental sensitivity’ has a significant effect on behavioral intention and sustainable consumption behavior. Hypothesis test results show that environmental values ​​have a positive and significant effect on behavioral intention and sustainable consumption behavior. The results of the sobel test show that behavioral intention can mediate the relationship between environmental values ​​and the sustainable consumption behavior.